Physiomimetic Models of Adenomyosis - Gnecco, Juan S.; Brown, Alex T.; Kan, Ellen L.; Baugh, Lauren; Ives, Clara; Loring, Megan; Griffith, Linda G. (Seminars in Reproductive Medicine, 2020)
Adenomyosis remains an enigmatic disease in the clinical and research communities. The high prevalence, diversity of morphological and symptomatic presentations, array of potential etiological explanations, and variable response to existing interventions suggest that different subgroups of patients with distinguishable mechanistic drivers of disease may exist. These factors, combined with the weak links to genetic predisposition, make the entire spectrum of the human condition challenging to model in animals. Here, after an overview of current approaches, a vision for applying physiomimetic modeling to adenomyosis is presented. Physiomimetics combines a system's biology analysis of patient populations to generate hypotheses about mechanistic bases for stratification with in vitro patient avatars to test these hypotheses. A substantial foundation for three-dimensional (3D) tissue engineering of adenomyosis lesions exists in several disparate areas: epithelial organoid technology; synthetic biomaterials matrices for epithelial–stromal coculture; smooth muscle 3D tissue engineering; and microvascular tissue engineering. These approaches can potentially be combined with microfluidic platform technologies to model the lesion microenvironment and can potentially be coupled to other microorgan systems to examine systemic effects. In vitro patient-derived models are constructed to answer specific questions leading to target identification and validation in a manner that informs preclinical research and ultimately clinical trial design.
Keywords: adenomyosis; organoids; models of adenomyosis; tissue engineering; microfluidic device